Puji Rochjati Score in Improving Early Detection Skills of Maternal Emergencies - Dwi Ghita; Saharuddin, Saharuddin (Journal of Evidence-Based Community Health, 2024)
One indicator of the success of health development in Indonesia is seen from the maternal and infant mortality rates. Awareness and knowledge about the danger signs of pregnancy and childbirth are needed in the community to take immediate action to prevent complications of pregnancy and childbirth or even death of the mother and baby. The Pudji Rochjati score card contains complete information regarding data on pregnant women needed for high-risk screening/early detection, safe delivery planning data, post-delivery data for mothers and babies, a brief overview of the mother's condition during the postpartum period, and complete data related to family planning. in the poedji rochjati score card. Refreshment and technical development of early detection with a praise rochayati score as the method used in carrying out this activity. The counseling material consisted of early detection of maternal and neonatal emergencies with the Puji Rochayati score. After the counseling was carried out, there was an increase in the knowledge and skills of mothers and midwives in early detection of emergencies with a praise rochayati score.